KONDISI EKOSISTEM TERUMBU KARANG DI KAWASAN KONSERVASI LAUT DAERAH BINTAN TIMUR KEPULAUAN RIAU - Adriman Adriman; Ari Purbayanto; Sugeng Budiharsono; Ario Damar (Fakultas Perikanan dan Kelautan, Universitas Riau, 2012)
Coral reef ecosystems is one of the major coastal and marine ecosystems that haveecological value, economic and aesthetic. Unfortunately, the ecosystem continuesto come under pressure from a variety of activities such as fishing, tourism,pollution and other activities. This study aims to determine the condition of coralreef ecosystems in the Regional Marine Protected Area (RMPA) East Bintan.Observations of coral reefs is done using a modification of the square transectmethod and condition of coral reefs can be estimated by the percentage of livecoral cover approach. While the analysis of water quality refers to the APHA. Tosee the linkages between the biophysical environment-chemical characteristics ofwater with each of the locations used multivariable statistical analysis approach toPCA (Principal Component Analysis). The results show that coral reefs in theMarine Protected Area Region East Bintan including the condition of 'being' to'good'. This condition is caused by the pressure of population activities in the pastsuch as sea sand mining, leaching of bauxite tailings disposal, tailings sandmining land, and the impact of destructive fishing continues until the timeresearch was conducted. Meanwhile, the measured water quality is below the seawater quality standard for marine life. Further analysis of the factors in marineenvironment conditions with live coral cover showed that the live coral cover wasnegatively correlated with most variable environmental parameters such as flowvelocity, salinity, TSS, DO, BOD5, nitrate, sediment and algae. except fortemperature, brightness, and depth and phosphate positively correlated.